FEASIBILITY STUDY OF RAINBOW BURGER BUSINESS DEVELOPMENT (CASE STUDY: UD. RAINBOW BURGER, GAMPONG JAVA, KOTA LANGSA) - Dery Reza Miswari; Meri Andriani; Heri Irawan (Fakultas Teknik Universitas Samudra, 2022)
Burger Rainbow is one of the culinary businesses that market burgers with the appearance of bread that innovates colorful with varied and healthy bread fillings. Rainbow burger sales cover the Langsa City area and have a 4x4 m² area with one worker and six hours of work time/per day. Rainbow Burger sold up to 21 pcs/day. The problem with the Rainbow burger business is that the business feasibility has not been carried out while the owner of UD. Burger Rainbow wants to expand its business by adding three outlets. The purpose of the study was to analyze the feasibility of developing the Rainbow burger business regarding technology and financial aspects. The method used is NPV Net Present Value (NPV), Payback Period (PP), Internal Rate Of Return (IRR), Profitability Ratio (PR), and Break Even-Point (BEP). The results and discussion of the technical aspects of technology are all categorized as feasible, and the financial part is obtained by the Present Net Value (NPV), amounting to Rp. 21.435.626 with Payback Period (PP) investment costs that will return the capital in 1 year three days. The Internal Rate Of Return (IRR) value is 60.51%, the Profitability Ratio (PR) is 4.07, and BEP (Break Even-Point) at the time of sale to 248 units. The Rainbow burger business concludes that it is worth developing by adding three outlets.